Analisis Pengelolaan Media Sosial Instagram @translation.mega - November, Lintang Samudera; Kurniasari, Ni Gusti Ayu Ketut (Sadharananikarana: Jurnal Ilmiah Komunikasi Hindu, 2025)
This study aims to analyze the management of the Instagram account @translation.mega, owned by Mega Translation Service, a company providing professional translation services. In the digital era, social media plays a crucial role in marketing, brand building, and audience engagement. This research adopts a qualitative approach using Regina Luttrell’s theoretical framework, The Circular Model of Social Media (SoMe), which consists of four stages: Share, Optimize, Manage, and Engage. Data were collected through interviews, observations, and documentation of the activities on the @translation.mega Instagram account. The findings indicate that Mega Translation has implemented a well-structured social media strategy through content planning, visual and caption optimization, the use of content management tools, and active audience engagement via Instagram features. Through effective social media management, the account has not only increased user engagement but also strengthened the company’s image and professionalism as a translation service provider.